Insights on tax compliance behaviour among businesswomen in Kano State, Nigeria - Isah, Maryam Muhammed (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
Previous studies reported tax non-compliance among SMEs is a major factor responsible for the low national tax revenue in many developing economies with flawed tax system. Consequently, revenue available to the government for the provision of public goods and services in such economies is also low. Nigeria, an example, is faced with challenges of low national tax revenue and a tax to GDP ratio due to high level of tax non-compliance among its businesswomen-dominated SMEs. An understanding of behavioural factors that influence the tax compliance decisions of SMEs will help policy makers to improve overall tax compliance and grow tax revenue. This study explores SMEs' tax knowledge and tax compliance factors (i.e., attitude, subjective norms and perceived behavioural control) related to Theory of Planned Behaviour (TPB) of female-owned SMEs in Nigeria using semi-structured interview method. Thematic analysis of data generated is done with the aid of Atlas.ti 8 software. The results reveal a mix of lower and higher level of tax knowledge among the businesswomen in SMEs. TPB factors also have a mixed of favourable and unfavourable influences on SMEs’ compliance decisions. Specifically, an unfavourable attitude expressed in the form of perception of fairness and low perceived government usage of the tax revenue was found to encourage tax non-compliance. Uncertainties and lack of transparency in the tax system are sources of complexities that may decrease tax compliance. Other factors, e.g., individual financial constraint, culture, gender and e-commerce also influence SMEs compliance behaviour. However, awareness about penalties for non-compliance (deterrence theory) is high and a strong reason that encourages tax compliance among the female businessowners. It is suggested that the Nigerian tax authority sustain the use of deterrence, reduce uncertainties and improve accountability and transparency in the tax system to improve tax compliance and earn the trust of the SME taxpayers.